Epidemiological studies of brucellosis, campylobacteriosis and trichomonosis, and other factors affecting calving rate in cattle herds in northern Nigeria - Thompson, P.N. (Peter N.) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.